2009
DOI: 10.1016/j.ydbio.2008.12.025
|View full text |Cite
|
Sign up to set email alerts
|

The physical state of fibronectin matrix differentially regulates morphogenetic movements in vivo

Abstract: This study demonstrates that proper spatiotemporal expression and the physical assembly-state of fibronectin (FN) matrix play key roles in the regulation of morphogenetic cell movements in vivo. We examine the progressive assembly and 3D fibrillar organization of FN and its role in regulating cell and tissue movements in Xenopus embryos. Expression of the 70 kD N-terminal fragment of FN blocks FN fibril assembly at gastrulation but not initial FN binding to integrins at the cell surface. We find that fibrillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 62 publications
3
102
0
Order By: Relevance
“…The mild defects induced by FF in mesodermal morphogenesis are in contrast to the severe defects induced in the AC and in agreement with the requirement of fibrillar FN for epiboly but not for convergent extension (Davidson et al, 2006;Marsden and DeSimone, 2001;Rozario et al, 2009). Here, we show that, despite the presence of a fibrillar matrix, both radial intercalation and cell polarity are lost in FF expressors, suggesting that an integrin-dependent polarizing signal is required for both processes.…”
Section: Research Articlesupporting
confidence: 88%
See 2 more Smart Citations
“…The mild defects induced by FF in mesodermal morphogenesis are in contrast to the severe defects induced in the AC and in agreement with the requirement of fibrillar FN for epiboly but not for convergent extension (Davidson et al, 2006;Marsden and DeSimone, 2001;Rozario et al, 2009). Here, we show that, despite the presence of a fibrillar matrix, both radial intercalation and cell polarity are lost in FF expressors, suggesting that an integrin-dependent polarizing signal is required for both processes.…”
Section: Research Articlesupporting
confidence: 88%
“…We postulated that this is due to the fact that in the absence of radial intercalation and BCR thinning, the mesodermal belt and the blastopore are held back, unable to move vegetally. This, coupled with the fact that mediolateral intercalation proceeds normally, leads to constriction of the embryo at the equatorial region and produces the characteristic mushroom-shaped embryos also seen in the 70 kDa FN experiments (Rozario et al, 2009). If this explanation is correct, one would expect increased tension in FF ACs.…”
Section: Epiboly Plays An Essential But Permissive Role During Xenopumentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, aligned ECM fibrils appear to orient mesodermal cell migration on the BCR through a contact guidance mechanism (Nakatsuji and Johnson, 1984). This mechanism appears to involve fibronectin (FN), which is a major component of the BCR fibrillar network (Boucaut and Darribere, 1983;Davidson et al, 2004;Johnson et al, 1992); blockage of FN synthesis, function or fibrillar assembly, as well as abrogation of the integrin α5β1 receptor, leads to abnormal adhesion, spreading and migration of mesodermal cells (Boucaut et al, 1990;Darribere and Schwarzbauer, 2000;Davidson et al, 2002;Nagel and Winklbauer, 1999;Rozario et al, 2009). Upon contact with FN, mesodermal cells relocalise their intrinsic protrusive activity along the BCR surface and replace filopodia with lamelliform protrusions (Winklbauer and Keller, 1996;Winklbauer and Nagel, 1991;Winklbauer and Selchow, 1992).…”
Section: Ecm-and Cell Contact-guided Migration During Developmentmentioning
confidence: 99%
“…It has been reported that the assembly and three-dimensional fibrillar organization of FN regulate cell adhesion, spreading and migration in Xenopus embryos (Darribere and Schwarzbauer, 2000;Rozario et al, 2009). The 70-kD N-terminal fragment of FN (70 kD-FN) was shown to obstruct FN matrix formation (Rozario et al, 2009). We confirmed that 70 kD-FN perturbed the formation of the FN fibrils in vitro and in zebrafish embryos (supplementary material Fig.…”
Section: Stat3-efemp2a Controls the Configuration Of The Ecm For The mentioning
confidence: 99%